Pengaruh Perceived Burdensomeness, Thwarted Belongingness, dan Religiusitas Terhadap Ideasi Bunuh Diri pada Lansia - Desy Ramadhani Harahap; Ilmi Amalia (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
Suicidal ideation in elderly is rarely a society’s concern even though elderly is the age group most vulnerable to suicide. This study was conducted to prove the effect of perceived burdensomeness, thwarted belongingness, religiosity, and demographic factors (gender and education level) on suicidal ideation in the elderly. The subjects of this study were 230 respondents aged 60 years and over who were obtained using accidental non-probability sampling techniques. The measuring instrument used were the adaptation and modification of the Geriatric Suicide Ideation Scale, the Interpersonal Needs Questionnaire, and the Centrality of Religiosity Scale. The validity test of the instrument was carried out using Confirmatory Factor Analysis (CFA), while the hypothesis testing was carried out using multiple regression analysis. The results showed that there was a significant effect of perceived burdensomeness and the ideological dimensions of religiosity. The results of this study are expected to be an input for readers to pay more attention to the perceived burdensomeness and ideology of religiosity in the elderly as factors that can influence suicidal ideation. Subsequent researchers can also develop this research by adding other independent variables to be analyzed, such as health conditions and living arrangements.